ЖОҚАРЫ ТӘЖРИЙБЕЛИ ПАЛЎАНЛАРДЫҢ ШАҚҚАНЛЫҒЫН АСЫРЫЎ УСЫЛЛАРЫ - Еримбетов, Б.Қ. (FAN va JAMIYAT, 2022)
In article is studied, perfection of dexterity of the qualified fighters the essence and the maintenance of problems reveals by preparation of fighters in achievement of high indicators. The role and value of physical factors is analyzed at a precompetitive stage.